2019
DOI: 10.1029/2018jc014360
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Removal of a Coastal Flood Deposit

Abstract: During floods, small mountainous rivers transport large sediment loads to the coastal ocean. This sediment often deposits near shore, and if conditions allow, various types of gravity flows (including hyperpycnal river plumes) can transport the sediment across the shelf within minutes to months of delivery. The stochastic and energetic nature of small‐mountainous‐river flood dispersal presents challenges to observations of transport processes and flood‐deposit formation during events, however. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…In such high efficiency transfer zones, the direct connection between terrestrial outflow and submarine canyon would be expected to result in a concentration of microplastics; in particular the larger size fractions but potentially also microfibers. If a river lacks a direct connection to a submarine canyon ( Figures 5B-D), then along-shelf currents and wave action can redistribute and disperse sediments, thus reducing the efficiency of the river to slope connectivity (Mulder et al, 2012;Eidam et al, 2019). These systems may be termed 'buffered, ' with the input conditions being less faithfully recorded in the sink ( Figure 6); an example being the Indus River -Indus Submarine Fan (Romans et al, 2016).…”
Section: How Might Terrestrial Microplastics Be Introduced To Deep-sementioning
confidence: 99%
“…In such high efficiency transfer zones, the direct connection between terrestrial outflow and submarine canyon would be expected to result in a concentration of microplastics; in particular the larger size fractions but potentially also microfibers. If a river lacks a direct connection to a submarine canyon ( Figures 5B-D), then along-shelf currents and wave action can redistribute and disperse sediments, thus reducing the efficiency of the river to slope connectivity (Mulder et al, 2012;Eidam et al, 2019). These systems may be termed 'buffered, ' with the input conditions being less faithfully recorded in the sink ( Figure 6); an example being the Indus River -Indus Submarine Fan (Romans et al, 2016).…”
Section: How Might Terrestrial Microplastics Be Introduced To Deep-sementioning
confidence: 99%
“…During the calm weather, the thickness of the FM was observed with a tidally averaged mean value of <0.3 m around the Changjiang Estuary and its adjacent coastal regions (Ge et al, 2018; X. Yang et al, 2015). Under some deposition events, much thicker FMs could occur, evidenced by previously recorded studies of the Waipaoa River shelf, the northern California shelf, the Eel River shelf, the Louisiana shelf, and the Elwha River (Eidam et al, 2019; Hale et al, 2014; Ogston et al, 2000; Traykovski et al, 2000, 2015). However, it is a considerable challenge to monitor and simulate the FM features under extreme weather conditions, particularly during a storm event (McAnally et al, 2007; Wan et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…6d). Additionally, the strong tidal currents of the Elwha River delta setting, which are responsible for export of the majority of sediment off of the submarine delta 21,2830 , may inhibit sand wave and spit formation by preventing the submarine formation of these features.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial mass balance showed that only about 5.4 Mt of this sediment could be accounted for in the subaerial, intertidal and subtidal regions of the river delta 21,22 . The remaining ~13 Mt of sediment was transported offshore of the submarine delta and dispersed broadly in the Strait of Juan de Fuca, largely owing to the strong tidal circulation of the region that regularly mobilizes sand and finer sediment 2830 . In the end, the release of sediment had wide-ranging effects on turbidity, sediment flux, morphodynamics and ecosystem change within the Elwha’s riparian, estuarine and coastal systems 22,3134 .…”
Section: Introductionmentioning
confidence: 99%